2001 : a space odyssey - Krämer, Peter (BFI film classics., 2010)
"Stanley Kubrick's 2001: A Space Odyssey is widely regarded as one of the best films ever made. Based on new research in the recently opened Stanley Kubrick Archive, this study challenges many of the widely held assumptions about the film, addressing how such a seemingly radical project managed to gain studio funding and why the film took the shape it finally did. Kramer also explores the film's close links to many of the most successful trends in Hollywood filmmaking across the 1950s and 60s, and to public debates about the space race and the search for extra-terrestrial intelligence. After examining what was described at the time as one of MGM's biggest ever promotional campaigns, Kramer documents the film's enormous and ever growing success with both critics and audiences across the late 1960s and early 70s, and its longterm impact on Hollywood's output of Science Fiction movies"--